Cation exchange membrane and method for producing the same
By using polyolefin-based woven fabric substrate and an appropriate amount of polyvinyl chloride in the cation exchange membrane, combined with the impregnation and copolymerization process, the problems of reduced strength and increased resistance at high temperatures are solved, and the resin is tightly attached Improvement of performance and resistance performance.
Patent Information
- Application Number
- CN202180021608.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-25
- Filing Date
- 2021-03-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-03-08
AI Technical Summary
When manufacturing a cation exchange film, the polyolefin resin-based substrate is damaged at high temperature, resulting in a decrease in strength. When the substrate is thickened to maintain strength, the film resistance increases, and the ion exchange resin and the substrate are poor integrity. , resulting in resin swelling and peeling problems.
A base material composed of a polyolefin-based woven fabric contains 23% or more than 35% or less of polyvinyl chloride on the outside, and a cation exchange resin having a sulfonic acid group is formed by an impregnation step and a copolymerization step, preferably at 40°C or more and Copolymerization is carried out at below 80°C and polyvinyl chloride is combined to improve the firmness of the resin to the substrate and the resistance of the film.
It effectively suppresses the swelling of the ion exchange resin, maintains the strength of the cation exchange membrane, and controls the membrane resistance to a low level, ensuring the durability and electrodialysis performance of the membrane.
Smart Images

Figure BDA0003847771050000221 
Figure BDA0003847771050000231
Abstract
Description
Technical Field
[0001] The invention relates to a cation exchange membrane and a method for manufacturing the same. Background Art
[0002] Ion exchange membrane is a film made of ion exchange resin into a film, but because it has a cross-linked structure, it is mechanically fragile if used directly. Therefore, in order to improve mechanical strength, a porous substrate having a function as a reinforcement is used to form a structure in which an ion exchange resin layer is arranged with the substrate as a core. As a method for manufacturing such an ion exchange membrane, a so-called paste method is known, according to which a polymerizable monomer slurry having an ion exchange group or capable of introducing an ion exchange group is applied on a substrate having a function as a reinforcement, and then the monomer is polymerized, and then the ion exchange group is introduced as required, thereby manufacturing an ion exchange membrane (for example, with reference to patent document 1).
[0003] However, as a substrate having a reinforcing member function, polyolefin resins or polyvinyl chloride are generally used. Polyolefin resins are superior to polyvinyl chloride in terms of alkali resistance, strength and heat resistance. Therefore, in ion exchange membranes used in fields requiring alkali resistance, strength and heat resistance, polyolefin resins are used as substrates. Such polyolefin resin substrates are mostly used in the form of woven fabrics, non-woven fabrics, porous sheets, etc.
[0004] However, although the polyolefin resin substrate is excellent in alkali resistance, strength and heat resistance, it has the disadvantage of poor adhesion to the ion exchange resin obtained by polymerizing a polymerizable monomer and introducing an ion exchange group as needed. Therefore, the swelling or deformation of the ion exchange resin cannot be suppressed, and the substrate and the ion exchange resin are easily peeled off due to repeated bending, thereby failing to function as an ion exchange membrane.
[0005] Therefore, as disclosed in Patent Document 2, a technique has been found to improve the flexibility of an ion exchange membrane by polymerizing a polymerizable monomer at 110° C. or higher to improve adhesion.
[0006] Patent Document 1: Japanese Patent Publication No. 6-329815
[0007] Patent Document 2: Japanese Patent Publication No. 57-34017
[0008] Patent Document 3: Japanese Patent Publication No. JP-A-1997-1 Summary of the invention
[0009] -Technical problem to be solved by the invention-
[0010] However, if polymerization is performed at 110°C or higher, the polyolefin resin substrate itself is damaged, thereby reducing the strength of the polyolefin resin substrate. If the substrate is thickened to maintain the strength, the membrane resistance (resistance) as an ion exchange membrane increases.
[0011] The present invention is completed to solve the above-mentioned technical problems, and its purpose is to provide a cation exchange membrane, which uses a polyolefin substrate, can inhibit the swelling of the ion exchange resin, and has a low electrical resistance.
[0012] -Technical solutions to technical problems-
[0013] The cation exchange membrane of the present invention comprises a substrate composed of a polyolefin woven fabric and a cation exchange resin having a sulfonic acid group, wherein the cation exchange membrane contains 23% by mass or more and 35% by mass or less of polyvinyl chloride in a portion other than the substrate.
[0014] The structure may be such that the resistance measured at 25°C using 0.5M saline is 1.5Ω·cm 2 Above 3.5Ω·cm 2 The breaking strength is 0.5 MPa to 1.2 MPa, the thickness of the substrate is 90 μm to 160 μm, and the opening ratio of the substrate is 35% to 50%.
[0015] The substrate may be composed of a monofilament polyethylene woven fabric.
[0016] Alternatively, the cation exchange resin may be a polystyrene cation exchange resin.
[0017] The cation exchange resin may contain a component derived from α-alkylstyrene.
[0018] The method for manufacturing a cation exchange membrane of the present invention is constructed as follows: it includes an impregnation step and a copolymerization step. In the above-mentioned impregnation step, a polymerizable composition for forming a cation exchange resin is impregnated into a substrate composed of a polyolefin woven fabric, and the above-mentioned polymerizable composition contains monomer components, a polymerization initiator and polyvinyl chloride. The above-mentioned monomer components include monomers having functional groups capable of introducing sulfonic acid groups or sulfonic acid groups and cross-linking monomers. In the above-mentioned copolymerization step, after the above-mentioned impregnation step, the above-mentioned monomer components in the polymerizable composition for forming the cation exchange resin are copolymerized; in the above-mentioned polymerizable composition for forming the cation exchange resin, the above-mentioned polyvinyl chloride is contained in an amount of not less than 55 parts by mass and not more than 98 parts by mass relative to 100 parts by mass of the above-mentioned monomer components.
[0019] In the copolymerization step, the copolymerization is preferably performed at a temperature of 40°C or higher and lower than 80°C.
[0020] The substrate may be composed of a monofilament polyethylene woven fabric.
[0021] The monomer having a functional group into which a sulfonic acid group can be introduced or a sulfonic acid group may be a styrene-based monomer having a functional group into which a sulfonic acid group can be introduced or a sulfonic acid group.
[0022] The monomer components may contain α-alkylstyrene, and the amount of the α-alkylstyrene may be 1% by mass or more and 13% by mass or less based on the total amount of the monomer components.
[0023] -Effects of the Invention-
[0024] The cation exchange membrane of the present invention uses a substrate composed of a polyolefin woven fabric and contains 23% to 35% by mass of polyvinyl chloride in the portion other than the substrate, so that both the suppression of swelling of the ion exchange resin and low resistance can be achieved. DETAILED DESCRIPTION
[0025] The preferred embodiments below are merely examples for describing the present invention in essence, and are not intended to limit the present invention, its application objects, or its uses.
[0026] (First Embodiment)
[0027] As described in the background technology section, polyolefin resins or polyvinyl chloride are used as the substrate of the cation exchange membrane. Moreover, in the case where alkali resistance, strength and heat resistance are required as the cation exchange membrane, polyolefin resins are used. In such a case, polyvinyl chloride is usually not selected. However, if a substrate of polyolefin resin is used, the adhesion to the cation exchange resin is poor, so there is a problem of the cation exchange resin peeling off from the substrate after swelling with water. The inventor of the present application has conducted various studies to solve this problem and thought of the present invention using a substrate of polyolefin woven fabric and polyvinyl chloride.
[0028] The cation exchange membrane according to the first embodiment includes a substrate made of a polyolefin woven fabric and a cation exchange resin having sulfonic acid groups as cation exchange groups, and contains 23% to 35% by mass of polyvinyl chloride in a portion other than the substrate.
[0029] <Polyolefin fabric>
[0030] As polyolefins, homopolymers of α-olefins such as ethylene, propylene, 1-butene, and 4-methyl-1-pentene or random or block copolymers thereof can be cited. Specifically, low-density polyethylene, high-density polyethylene, polypropylene, poly-1-butene, and poly-4-methyl-1-pentene can be cited. Among them, low-density polyethylene, high-density polyethylene, and polypropylene are preferred. From the perspective of ease of acquisition and drug resistance, polyethylene polymers such as low-density polyethylene or high-density polyethylene are most preferred.
[0031] The polyolefin substrate can have any form such as woven fabric, non-woven fabric, porous membrane, etc., but from the viewpoint of strength, woven fabric is preferred. The opening ratio of the woven fabric is preferably 35% to 50%. As the single yarn of the woven fabric, any of multifilament and monofilament can be used, but from the viewpoint of reducing the contact area with the ion exchange resin, that is, reducing the gap between the ion exchange resin and the substrate, monofilament is preferred. From the viewpoint of balancing the strength and the membrane resistance, the thickness of the polyolefin woven fabric is preferably 90 μm to 160 μm, and the wire diameter of the single yarn is preferably 1 to 70 denier (10 to 100 μm), but it can be appropriately selected according to the application.
[0032] <Cation exchange resin>
[0033] The cation exchange resin having sulfonic acid groups that forms the cation exchange membrane is a known substance, for example, a substance in which sulfonic acid groups are introduced into the resin forming the skeleton. As the resin forming the skeleton, for example, polymers and copolymers thereof obtained by polymerizing monomers having ethylene unsaturated double bonds such as vinyl, styrene, acrylic acid, and hydrocarbon resins such as polymers containing aromatic rings in the main chain such as polysulfone, polyphenylene sulfide, polyether ketone, polyether ether ketone, polyether imide, polyphenylene ether, polyether sulfone, polybenzimidazole, etc. can be cited. Among them, as the resin forming the skeleton, a styrene cation exchange resin based on styrene monomers is preferred.
[0034] The cation exchange group is specifically a sulfonic acid group. The sulfonic acid group is a strongly acidic group, which is strongly negatively charged in an aqueous solution and exhibits a strong cation exchangeability. Therefore, a cation exchange membrane having a sulfonic acid group can be particularly advantageously used in various applications requiring cation exchangeability. On the contrary, the problem of low affinity and poor adhesion to a polyolefin resin substrate becomes more significant. The problem of poor adhesion can be well improved by adding a specific amount of polyvinyl chloride to a cation exchange resin, so the effect of the present invention is particularly significantly exerted, so it is preferred.
[0035] <Polyvinyl chloride>
[0036] As the polyvinyl chloride, known polyvinyl chloride can be used without any limitation. For example, as long as the characteristics of the polyvinyl chloride or the purpose of the present embodiment are not impaired, not only homopolymers of vinyl chloride but also copolymers obtained by copolymerization of other monomers can be used. As copolymerizable monomers, α-olefins such as ethylene and propylene, vinyl esters such as vinyl acetate, etc. can be generally cited. Of course, these polyvinyl chlorides can be used alone, or two or more can be used in combination.
[0037] The chlorine content of polyvinyl chloride is preferably in the range of 30 to 80% by mass, and particularly preferably in the range of 55 to 70% by mass. When the chlorine content is in this range, the affinity for styrene is high, and thus it functions advantageously in the above-mentioned bonding mechanism.
[0038] From the viewpoint of heat resistance, a material having a high softening point, for example, a Clash-Berg softening temperature (JIS K6734) of 60°C or more, more preferably 65°C or more, is suitable. This is because a material that meets the above range can maintain high adhesion even at high temperatures, so that even when electrodialysis is performed under high temperature conditions, membrane peeling does not occur, and electrodialysis can be performed stably. The Clash-Berg softening temperature is usually 70°C or less.
[0039] The average degree of polymerization of polyvinyl chloride is not particularly limited, and is generally preferably in the range of 500 to 3000, and particularly preferably in the range of 800 to 2000. The longer the molecular chain of polyvinyl chloride, the greater the degree of entanglement with molecules such as cation exchange resins, thereby obtaining high adhesion, but if the molecular chain is too long, the solubility in the solvent will decrease. Polyvinyl chloride having an average degree of polymerization within the above range can obtain high adhesion and can obtain a cation exchange membrane that does not leak.
[0040] Polyvinyl chloride can be used in a known form such as powder or granule, preferably powdered polyvinyl chloride, more preferably powdered polyvinyl chloride having an average particle size of 0.1 μm to 30 μm when measured by laser diffraction scattering method. This is because powdered polyvinyl chloride has good affinity with the resin forming the skeleton described later and is easy to disperse uniformly. Such polyvinyl chloride powder can be obtained by a known suspension polymerization method.
[0041] Polyvinyl chloride has an extremely high affinity for monomers such as styrene or crosslinking agent components such as divinylbenzene, so it is particularly preferable to use a cation exchange resin obtained by sulfonating a styrene-divinylbenzene copolymer as the cation exchange resin. This is because polyvinyl chloride is polymerized in a state where it is compatible with a monomer having a sulfonic acid group or a monomer having a reactive group capable of introducing a sulfonic acid group or a crosslinking monomer, so that polyvinyl chloride exists in a state of being entangled with the molecular chain of the cation exchange resin, thereby effectively preventing the polyvinyl chloride from being detached, and effectively suppressing the swelling of the ion exchange resin by using polyvinyl chloride.
[0042] It is necessary to contain polyvinyl chloride of more than 23 mass % and less than 35 mass % in the part other than the substrate in the cation exchange membrane (relative to the dry mass). It is preferably more than 24 mass % and less than 32 mass %, and more preferably more than 25 mass % and less than 29 mass %. If the amount of polyvinyl chloride is too little, the swelling of the cation exchange membrane becomes large and is easy to peel off. If the amount of polyvinyl chloride is too much, it is possible to produce undesirable conditions such as increased resistance of the membrane.
[0043] In particular, from the viewpoint of efficient electrodialysis, the resistance of the cation exchange membrane is 1.5 Ω·cm 2 Above 3.5Ω·cm 2 Below, preferably 1.5Ω·cm 2 Above 3.2Ω·cm 2 Below, more preferably 1.5Ω·cm 2 Above 3.0Ω·cm 2 the following.
[0044] The peeling of the resin will also increase the amount of water permeation, which will reduce the current efficiency in electrodialysis. The water permeation value measured using 0.1 MPa pressurized water is 600 ml / (m 2 ·hr) or less, preferably 500ml / (m 2 ·hr) or less, more preferably 300ml / (m 2 hr) or less.
[0045] <Manufacturing of cation exchange membrane>
[0046] The cation exchange membrane according to the present embodiment is produced as follows.
[0047] A polymerizable composition is prepared by mixing a monomer having a sulfonic acid group, a crosslinking monomer, a polymerization initiator and other polymerizable curable components for forming a cation exchange resin with polyvinyl chloride. A polyolefin woven fabric as a substrate is impregnated with the polymerizable composition and the polymerizable composition is filled into the gaps of the woven fabric. The polymerizable composition is polymerized and cured to produce a cation exchange resin. In this way, the target cation exchange membrane can be obtained.
[0048] In order to suppress the thermal aging of polyolefin fabrics, the polymerization curing temperature is preferably set to a temperature much lower than the melting point of the polyolefin fabric. Although it also depends on the type of polyolefin, polymerization curing component, and polymerization curing time, the upper limit of the polymerization curing temperature is preferably set to a temperature 40°C lower than the melting point of the polyolefin constituting the substrate. Specifically, the polymerization curing temperature is preferably above 40°C and below 80°C, and more preferably above 50°C and below 80°C. If the polymerization is carried out at too low a temperature, the polymerization of the monomer cannot be fully carried out, the unpolymerized part increases and dissolves, and voids are generated, which may lead to a decrease in current efficiency. On the other hand, if the temperature is too high, the temperature exceeds the melting point of the polyolefin, and the strength of the polyolefin resin substrate may be reduced.
[0049] The monomer with sulfonic acid group in the polymerization curing component can be a monomer that has been used for the manufacture of cation exchange resin. For example, sulfonic acid monomers such as α-halogenated vinyl sulfonic acid, styrene sulfonic acid, vinyl sulfonic acid, their salts and esters, etc. can be cited. Relative to all monomer components, the amount of monomers with sulfonic acid group is preferably 30 mass % or more and 98 mass % or less, more preferably 40 mass % or more and 90 mass % or less. It should be noted that, as a part of the monomer, it is preferred to contain α-alkyl styrene, and relative to all monomer components, the amount of α-alkyl styrene is preferably 1 mass % or more and 13 mass % or less. By containing α-alkyl styrene, it is possible to suppress the rapid polymerization, thereby preventing the polymerization curing temperature from suddenly rising to above the target temperature.
[0050] The crosslinking monomer is used to densify the cation exchange resin, improve the swelling inhibition, membrane strength, etc., and is not particularly limited. Examples thereof include divinyl compounds such as divinylbenzene, divinylsulfone, butadiene, chloroprene, divinylbiphenyl, trivinylbenzenes, divinylnaphthalene, diallylamine, and divinylpyridine. Usually, such a crosslinking monomer is preferably blended in an amount of 0.1 to 50% by mass, and more preferably 1 to 40% by mass, relative to the total monomer components.
[0051] In addition to the above-mentioned monomers having sulfonic acid groups and crosslinking monomers, other monomers copolymerizable with these monomers may be added as needed. As other monomers, for example, styrene, chloromethylstyrene, acrylonitrile, methylstyrene, ethylvinylbenzene, acrolein, methylvinyl ketone, vinylbiphenyl, etc. may be used. The amount of other monomers varies depending on the purpose of addition. Generally, other monomers are preferably added in an amount of 0 to 50% by mass relative to the total monomer components, and in particular, in the case of imparting flexibility, other monomers are preferably added in an amount of 5 to 40% by mass.
[0052] As the polymerization initiator, a conventionally known polymerization initiator can be used without particular limitation, and a polymerization initiator having a 10-hour half-life temperature of less than 80° C. is preferred. Specifically, organic peroxides such as diisobutyl peroxide, di(3,5,5-trimethylhexanoyl) peroxide, dilauroyl peroxide, disuccinic acid peroxide, and benzoyl peroxide can be used. It is preferred to mix 0.1 to 20 parts by mass of the polymerization initiator, and more preferably 0.5 to 10 parts by mass of the polymerization initiator, relative to 100 parts by mass of the monomer component.
[0053] Polyvinyl chloride is added to the above-mentioned polymerizable curable component in such a manner that the finally obtained cation exchange membrane has the above-mentioned composition to prepare a polymerizable composition. Specifically, with respect to 100 parts by mass of the monomer component, it is preferred to add 55 parts by mass or more and 98 parts by mass or less of polyvinyl chloride (preferably in powder form). It is more preferably 57 parts by mass or more and 86 parts by mass or less, and particularly preferably 60 parts by mass or more and 75 parts by mass or less. There is no particular limitation on the method of adding polyvinyl chloride, and the polyvinyl chloride and the polymerizable curable component can be stirred at room temperature until a uniform polymerizable composition is formed, or the temperature can be heated to a temperature at which the polymerizable curable component does not polymerize, specifically, heated to a temperature below 40°C and then stirred and mixed.
[0054] The polymerizable composition may contain a chlorinated polyolefin, a thickener, a known additive, and the like as necessary.
[0055] Examples of the thickener include polyolefin powders having an average particle size of 10 μm or less, saturated aliphatic hydrocarbon polymers such as ethylene-propylene copolymers and polybutene, and styrene polymers such as styrene-butadiene copolymers. By using such a thickener, the viscosity can be adjusted within a range that effectively prevents sagging during film forming.
[0056] In addition, examples of additives include plasticizers such as dioctyl phthalate, dibutyl phthalate, tributyl phosphate, tributyl acetyl citrate, or alcohol esters of fatty acids or aromatic acids, hydrochloric acid scavengers such as styrene oxide and ethylene glycol diglycidyl ether, etc. The amount of the additive varies depending on the purpose of addition, and is preferably 0.1 to 50 parts by mass, particularly preferably 0.5 to 30 parts by mass, relative to 100 parts by mass of the monomer component.
[0057] The method for impregnating the voids of the substrate of the polyolefin woven fabric with the polymerizable composition is not particularly limited. For example, it can be performed by immersing the polyolefin substrate into a tank filled with the polymerizable composition. Of course, the polymerizable composition can also be impregnated by spraying, coating with a doctor blade, etc. instead of immersion.
[0058] As described above, the polymerizable composition impregnated into the polyolefin woven fabric is heated and copolymerized in a polymerization device such as a heating oven to be cured.
[0059] In the polymerization process, the following method is generally used: the polyolefin woven fabric filled with the polymerizable composition is sandwiched between films such as polyester, and the temperature is raised from room temperature under pressure. The pressurization is usually performed at a pressure of about 0.1 to 1.0 MPa by using an inert gas such as nitrogen or a roller. By performing this pressurization, the remaining polymerizable composition existing on the outer interface of the polyolefin woven fabric is polymerized while being pressed into the gaps of the polyolefin woven fabric, thereby effectively preventing the occurrence of resin retention.
[0060] Other polymerization conditions depend on the type of polymerization curable components, etc., and can be appropriately selected and determined from known conditions. As mentioned above, the polymerization temperature is set to a temperature much lower than the melting point of the polyolefin woven fabric (specifically, above 40°C and below 80°C). In addition, the polymerization time varies depending on the polymerization temperature, etc., but is usually about 3 to 20 hours. After the polymerization curing is completed, a cation exchange membrane supported on the polyolefin woven fabric is obtained.
[0061] In this embodiment, a cation exchange resin precursor resin-forming polymerizable curable component having a reactive group capable of introducing a sulfonic acid group can be used instead of a cation exchange resin-forming polymerizable curable component to form a cation exchange membrane. Specifically, a monomer having a reactive group capable of introducing a sulfonic acid group is added to a polymerizable composition instead of the above-mentioned monomer having a sulfonic acid group to produce a cation exchange membrane precursor. In this case, except for the addition of a sulfonic acid group introduction step described later, the cation exchange membrane precursor can be produced in the same manner as when a monomer having a sulfonic acid group is added.
[0062] In order to manufacture the cation exchange resin, as the monomer having a reactive group capable of introducing a sulfonic acid group, the monomers conventionally used can be used. For example, styrene, methylstyrene, vinylxylene, ethylvinylbenzene, α-alkylstyrene (specifically, α-methylstyrene), vinylnaphthalene, α-halogenated styrenes, etc. can be cited. It should be noted that as a part of the monomer, α-alkylstyrene is preferably contained, and the amount of α-alkylstyrene is preferably 1% by mass or more and 13% by mass or less relative to the total monomer components.
[0063] In addition to the monomer having a reactive group capable of introducing a sulfonic acid group and the crosslinking monomer, other monomers may be used as necessary. Examples of other monomers include chloromethylstyrene, acrylonitrile, acrolein, and methyl vinyl ketone.
[0064] The sulfonic acid group introduction step is performed after the polymerizable composition is polymerized and solidified to obtain a membrane of a cation exchange resin precursor resin. In this step, concentrated sulfuric acid or chlorosulfonic acid is allowed to act on the obtained precursor resin as a sulfonic acid group introduction agent, or hydrolysis or the like is performed in order to perform sulfonation, chlorosulfonation, etc., thereby introducing sulfonic acid groups. In this way, the target cation exchange membrane can be obtained.
[0065] In this embodiment, it is preferred to use a polymerizable curable component for forming a cation exchange resin precursor resin. This is because, in this embodiment, the cation exchange membrane is prepared from a polymerizable composition in which polyvinyl chloride is added to the polymerizable curable component, which is an important feature, but in the case of a polymerizable curable component without a sulfonic acid group introduced, polyvinyl chloride shows higher solubility than a polymerizable curable component with a sulfonic acid group introduced.
[0066] The thickness of the cation exchange membrane manufactured as described above is preferably in the range of 100 to 300 μm. If the thickness is too thin, the strength of the cation exchange membrane may be greatly reduced. If the thickness is too thick, it may cause problems such as increased resistance.
[0067] The burst strength of the cation exchange membrane depends on the thickness, but the filament diameter and thickness of the polyolefin woven fabric or the amount of the crosslinking monomer in the polymerization curable component can be adjusted to make the burst strength of the cation exchange membrane 0.5 MPa to 1.2 MPa.
[0068] In the cationic exchange membrane of the present embodiment, with polyolefin woven fabric as substrate, and partly contain polyvinyl chloride more than 23 mass % and less than 35 mass % beyond substrate.Like this, owing to contain a large amount of polyvinyl chloride, therefore the monomer as the raw material of cationic exchange resin enters the inside of polyvinyl chloride powder etc., then carries out copolymerization, can suppress the degree of cationic exchange membrane water absorption swelling thus, prevents substrate and cationic exchange resin from peeling off.Therefore, even do not increase the thickness of substrate also can improve the intensity of cationic exchange membrane overall.Because cationic exchange resin and polyvinyl chloride are integrated as mentioned above, therefore polyvinyl chloride can not block the opening of substrate, can suppress the resistance increase of cationic exchange membrane.
[0069] The cation exchange membrane of the present invention having such properties can be well applied in many fields: as an electrodialysis membrane used in desalination processes in the salt production and food fields, an electrolyte membrane for fuel cells, and a diffusion dialysis membrane used when recovering acid from acids containing metal ions produced in the steel industry, etc.
[0070] Example
[0071] The excellent effects of the present invention are described below. In the examples and comparative examples, the characteristics of the ion exchange membranes were obtained by the following measurements.
[0072] 1) Polyvinyl chloride content in cation exchange resin
[0073] The ion exchange membrane was dried under reduced pressure at 60° C. for 5 hours, and the weight (Dg) at the time of drying was measured.
[0074] Next, the same ion exchange membrane was immersed in a 0.5 mol / l FeCl2 aqueous solution for more than 1 hour, and then fully washed with ion exchange water. Then, it was immersed in a 10 mass % hydrogen peroxide solution for more than 6 hours, and the obtained solid content was recovered by a filter.
[0075] Next, the solid content was washed with acetone to recover the substrate, which was then dried at 60° C. for 3 hours, and the dry weight (Bg) of the substrate was measured.
[0076] Next, acetone was distilled off from the acetone washing liquid using an evaporator, and the solid component obtained was analyzed by infrared spectroscopy to confirm that it was polyvinyl chloride. Then, the dry weight (Yg) of the obtained polyvinyl chloride was measured. Based on the above measured values, the polyvinyl chloride content in the resin of the ion exchange membrane was calculated by the following formula.
[0077] Polyvinyl chloride content = 100 × Y / (DB) [%]
[0078] 2) Water seepage of ion exchange membrane
[0079] The ion exchange membrane was sandwiched in a cylindrical battery, 50 ml of water was added to the top, and a pressure of 0.1 MPa was applied to the top of the ion exchange membrane. The amount of water Wpw that permeated the ion exchange membrane within 1 hour was measured, and the water permeation was calculated according to the following formula. At this time, the effective area of the membrane was 12.6 cm 2 .
[0080] Water seepage (ml / m 2 ×hr)=Wpw / (S×t)
[0081] Where, S: effective area of membrane (m 2 ), t: test time (hours).
[0082] 3) Ion exchange capacity and water content of ion exchange membrane
[0083] The ion exchange membrane was immersed in a 1 mol / l HCl aqueous solution for 10 hours or more.
[0084] Then, the counter ions of the ion exchange groups were replaced from hydrogen ions to sodium ions using a 1 mol / l NaCl aqueous solution, and the free hydrogen ions were quantified (Amol) using a potentiometric titrator for sodium hydroxide solution (AT-710, manufactured by Kyoto Electronics Co., Ltd.).
[0085] Next, the same ion exchange membrane was immersed in a 1 mol / l NaCl aqueous solution for more than 4 hours and then fully washed with ion exchange water. The surface moisture was then wiped off with tissue paper, and the mass (Wg) of the wet membrane was measured. Furthermore, the membrane was dried under reduced pressure at 60°C for 5 hours, and the weight (Dg) when dry was measured. Based on the above measured values, the ion exchange capacity and water content of the ion exchange membrane were calculated using the following formula.
[0086] Ion exchange capacity = A × 1000 / D [meq / g-dry mass]
[0087] Moisture content = 100 × (WD) / D [%]
[0088] 4) Thickness of ion exchange membrane
[0089] After the ion exchange membrane was immersed in a 0.5 mol / l NaCl aqueous solution for 4 hours or more, the water on the membrane surface was wiped off with a tissue paper, and the membrane was measured using a micrometer (MDE-25MX, manufactured by Mitsutoyo).
[0090] 5) Resistance of ion exchange membrane
[0091] The ion exchange membrane was sandwiched in a double-chamber cell with platinum black electrodes. Both sides of the ion exchange membrane were filled with 0.5 mol / l NaCl aqueous solution. The resistance between the electrodes at 25°C was measured using an AC bridge (frequency 1000 cycles / second). The membrane resistance (Ω·cm) was calculated from the difference between the electrode resistance and the electrode resistance when no ion exchange membrane was installed. 2 ). It should be noted that the ion exchange membrane used in the above measurement was an ion exchange membrane that had been pre-equilibrated in a 0.5 mol / l NaCl aqueous solution.
[0092] 6) Current efficiency of ion exchange membrane
[0093] A double-chamber cell was used, which sandwiched an ion exchange membrane. The cell structure was anode (Pt plate) (0.5 mol / l NaOH aqueous solution) / ion exchange membrane / (3.0 mol / l NaOH aqueous solution) cathode (Pr plate), and the current density was 10 A / dm at a solution temperature of 25°C. 2 After energizing for 1 hour, the solution on the anode side was recovered. The sodium hydroxide concentrations in the recovered solution and the initial solution were quantified using a potentiometric titrator (AT-710, manufactured by Kyoto Electronics Co., Ltd.) using a sulfuric acid aqueous solution, and the current efficiency was calculated using the following formula.
[0094] Current efficiency = (CB-CS) / (I×t / F)×100[%]
[0095] In the above formula, CB represents the concentration of the initial solution, CS represents the concentration of the recovered solution after power is applied, I represents the current value (A), t represents the power-on time (sec), and F represents the Faraday constant (96500C / mol).
[0096] 7) Bursting strength of ion exchange membrane
[0097] The ion exchange membrane was immersed in a 0.5 mol / l NaCl aqueous solution for more than 4 hours and then washed thoroughly with ion exchange water. The membrane was then not dried and the burst strength was measured using a Mullen burst tester (manufactured by Toyo Seiki) in accordance with JIS-P8112.
[0098] <Example 1>
[0099] A monomer mixture of the following formulation was prepared.
[0100] Styrene (St) 58.1 mass%
[0101] Chloromethylstyrene (CMS) 17.6 mass%
[0102] Divinylbenzene (DVB: purity 57%, the remainder is ethylvinylbenzene) 8.2 mass%
[0103] Acrylonitrile (AN) 13.1 mass%
[0104] α-Methylstyrene (α-MeSt) 3.0 mass%
[0105] The following substances were mixed into 100 parts by mass of the monomer mixture:
[0106] Ethylene glycol diglycidyl ether 0.8 parts by mass
[0107] Acetyl tributyl citrate (ATBC) 17.4 parts by mass
[0108] Lauroyl peroxide (Peroyl L manufactured by NOF CORPORATION) 2.0 parts by mass
[0109] Further addition:
[0110] Vinyl chloride powder (ZEST P22 manufactured by SHINDAI-ICHI VINYL CORPORATION) 65.3 parts by mass
[0111] The mixture was then stirred for 2 hours to obtain a uniform polymerizable composition.
[0112] Next, the following high-density polyethylene monofilament woven fabric (PE33D 120 / 120) was prepared.
[0113] High-density polyethylene monofilament fabric (PE33D 120 / 120);
[0114] Mesh number: 120
[0115] Fiber diameter: 76μm (33 denier)
[0116] Thickness: 132μm
[0117] Opening rate: 41%
[0118] Bursting strength: 1.0MPa
[0119] The polymerizable composition obtained in the above manner was coated on the above-mentioned high-density polyethylene monofilament woven fabric (PE33D 120 / 120), and after covering both sides of the above-mentioned high-density polyethylene monofilament woven fabric with polyester film as a release agent, it was preheated at 45°C for 1 hour and then polymerized at 70°C for 3 hours.
[0120] The obtained film-like polymer was sulfonated with chlorosulfonic acid at 40° C. for 45 minutes to obtain a cation exchange membrane. The properties of the obtained cation exchange membrane are as follows.
[0121] Polyvinyl chloride content in cation exchange resin: 26.1%
[0122] Film thickness: 220μm
[0123] Ion exchange capacity: 2.0meq. / g-dry weight
[0124] Moisture content: 47%
[0125] Resistance: 1.9Ω·cm 2
[0126] Water seepage: 30ml / (m 2 hr)
[0127] Current efficiency: 74%
[0128] Bursting strength: 0.9MPa
[0129] <Example 2>
[0130] A monomer mixture of the following formulation was prepared.
[0131] Styrene (St) 57.9 mass%
[0132] Chloromethylstyrene (CMS) 19.5 mass%
[0133] Divinylbenzene (DVB: purity 57%, the remainder is ethylvinylbenzene) 9.1 mass%
[0134] Acrylonitrile (AN) 10.5 mass%
[0135] α-Methylstyrene (α-MeSt) 3.0 mass%
[0136] The following substances were mixed into 100 parts by mass of the monomer mixture:
[0137] Ethylene glycol diglycidyl ether 0.8 parts by mass
[0138] Acetyl tributyl citrate (ATBC) 13.9 parts by mass
[0139] Lauroyl peroxide (Peroyl L manufactured by NOF CORPORATION) 2.0 parts by mass
[0140] Further addition:
[0141] Vinyl chloride powder (ZEST P22 manufactured by Shindai-ichi Vinyl Corporation) 63.4 parts by mass
[0142] The mixture was then stirred for 2 hours to obtain a uniform polymerizable composition.
[0143] Next, the following high-density polyethylene monofilament woven fabric (PE33D 120 / 120) was prepared.
[0144] High-density polyethylene monofilament fabric (PE33D 120 / 120);
[0145] Mesh number: 120
[0146] Fiber diameter: 76μm (33 denier)
[0147] Thickness: 132μm
[0148] Opening rate: 41%
[0149] Bursting strength: 1.0MPa
[0150] A cation exchange membrane was produced in the same manner as in Example 1 except that the polymerizable composition was changed to the above-mentioned composition.
[0151] The properties of the obtained cation exchange membrane are as follows.
[0152] Polyvinyl chloride content in cation exchange resin: 25.5%
[0153] Film thickness: 206μm
[0154] Ion exchange capacity: 2.1meq. / g-dry weight
[0155] Moisture content: 38%
[0156] Resistance: 2.6Ω·cm 2
[0157] Water seepage: 88ml / (m 2 hr)
[0158] Current efficiency: 83%
[0159] Bursting strength: 0.9MPa
[0160] <Example 3>
[0161] A monomer mixture of the following formulation was prepared.
[0162] Styrene (St) 45.4 mass%
[0163] Chloromethylstyrene (CMS) 19.6 mass%
[0164] Divinylbenzene (DVB: purity 57%, the remainder is ethylvinylbenzene) 9.1 mass%
[0165] Acrylonitrile (AN) 22.9 mass%
[0166] α-Methylstyrene (α-MeSt) 3.0 mass%
[0167] The following substances were mixed into 100 parts by mass of the monomer mixture:
[0168] Ethylene glycol diglycidyl ether 0.8 parts by mass
[0169] Acetyl tributyl citrate (ATBC) 17.4 parts by mass
[0170] Acrylonitrile butadiene rubber (NBR) 1.0 parts by mass
[0171] Lauroyl peroxide (Peroyl L manufactured by NOF CORPORATION) 2.0 parts by mass
[0172] Further addition:
[0173] Vinyl chloride powder (ZEST PQ135 manufactured by SHINDAI-ICHI VINYL CORPORATION) 72.0 parts by mass
[0174] The mixture was then stirred for 2 hours to obtain a uniform polymerizable composition.
[0175] Next, the following high-density polyethylene monofilament woven fabric (PE33D 120 / 120) was prepared.
[0176] High-density polyethylene monofilament fabric (PE33D 120 / 120);
[0177] Mesh number: 120
[0178] Fiber diameter: 76μm (33 denier)
[0179] Thickness: 132μm
[0180] Opening rate: 41%
[0181] Bursting strength: 1.0MPa
[0182] A cation exchange membrane was produced in the same manner as in Example 1 except that the polymerizable composition was changed to the above-mentioned composition.
[0183] The properties of the obtained cation exchange membrane are as follows.
[0184] Polyvinyl chloride content in cation exchange resin: 28.7%
[0185] Film thickness: 219μm
[0186] Ion exchange capacity: 1.7 meq. / g-dry weight
[0187] Moisture content: 43%
[0188] Resistance: 2.5Ω·cm 2
[0189] Water seepage: 183ml / (m 2 hr)
[0190] Current efficiency: 79%
[0191] Bursting strength: 0.9MPa
[0192] <Example 4>
[0193] A monomer mixture of the following formulation was prepared.
[0194] Styrene (St) 58.3 mass%
[0195] Chloromethylstyrene (CMS) 19.5 mass%
[0196] Divinylbenzene (DVB: purity 57%, the remainder is ethylvinylbenzene) 9.1 mass%
[0197] Acrylonitrile (AN) 13.1 mass%
[0198] The following substances were mixed into 100 parts by mass of the monomer mixture:
[0199] Ethylene glycol diglycidyl ether 0.8 parts by mass
[0200] Acetyl tributyl citrate (ATBC) 17.4 parts by mass
[0201] Lauroyl peroxide (Peroyl L manufactured by NOF CORPORATION) 2.0 parts by mass
[0202] Further addition:
[0203] Vinyl chloride powder (ZEST P22 manufactured by SHINDAI-ICHI VINYL CORPORATION) 55.0 parts by mass
[0204] The mixture was then stirred for 2 hours to obtain a uniform polymerizable composition.
[0205] Next, the following high-density polyethylene monofilament woven fabric (PE33D 100 / 100) was prepared.
[0206] High-density polyethylene monofilament fabric (PE33D 100 / 100);
[0207] Mesh number: 100
[0208] Fiber diameter: 76μm (33 denier)
[0209] Thickness: 132μm
[0210] Opening rate: 49%
[0211] Bursting strength: 0.9MPa
[0212] A cation exchange membrane was produced in the same manner as in Example 1 except that the polymerizable composition was changed to the above-mentioned composition.
[0213] The properties of the obtained cation exchange membrane are as follows.
[0214] Polyvinyl chloride content in cation exchange resin: 23.6%
[0215] Film thickness: 185μm
[0216] Ion exchange capacity: 2.3meq. / g-dry weight
[0217] Moisture content: 48%
[0218] Resistance: 1.7Ω·cm 2
[0219] Water seepage: 541ml / (m 2 hr)
[0220] Current efficiency: 72%
[0221] Bursting strength: 0.8MPa
[0222] <Example 5>
[0223] A cation exchange membrane was produced in the same manner as in Example 4 except that the amount of vinyl chloride powder (ZEST P22 manufactured by SHINDAI-ICHI VINYL CORPORATION) added to the monomer mixture was changed to 58.0 parts by mass.
[0224] The properties of the obtained cation exchange membrane are as follows.
[0225] Polyvinyl chloride content in cation exchange resin: 24.6%
[0226] Film thickness: 182μm
[0227] Ion exchange capacity: 2.3meq. / g-dry weight
[0228] Moisture content: 47%
[0229] Resistance: 1.8Ω·cm 2
[0230] Water seepage: 413ml / (m 2 hr)
[0231] Current efficiency: 73%
[0232] Bursting strength: 0.8MPa
[0233] <Example 6>
[0234] A cation exchange membrane was produced in the same manner as in Example 2, except that the amount of vinyl chloride powder (ZEST P22 manufactured by SHINDAI-ICHI VINYL CORPORATION) added to the monomer mixture was changed to 80.0 parts by mass.
[0235] The properties of the obtained cation exchange membrane are as follows.
[0236] Polyvinyl chloride content in cation exchange resin: 30.9%
[0237] Film thickness: 197μm
[0238] Ion exchange capacity: 2.1meq. / g-dry weight
[0239] Moisture content: 32%
[0240] Resistance: 3.1Ω·cm 2
[0241] Water seepage: 25ml / (m 2 hr)
[0242] Current efficiency: 86%
[0243] Bursting strength: 0.9MPa
[0244] <Example 7>
[0245] A cation exchange membrane was produced in the same manner as in Example 2, except that the amount of vinyl chloride powder (ZEST P22 manufactured by SHINDAI-ICHI VINYL CORPORATION) added to the monomer mixture was changed to 90.0 parts by mass.
[0246] The properties of the obtained cation exchange membrane are as follows.
[0247] Polyvinyl chloride content in cation exchange resin: 33.5%
[0248] Film thickness: 195μm
[0249] Ion exchange capacity: 2.1meq. / g-dry weight
[0250] Moisture content: 30%
[0251] Resistance: 3.3Ω·cm 2
[0252] Water seepage: 29ml / (m 2 hr)
[0253] Current efficiency: 87%
[0254] Bursting strength: 1.0MPa
[0255] <Example 8>
[0256] A monomer mixture of the following formulation was prepared.
[0257] Styrene (St) 58.1 mass%
[0258] Chloromethylstyrene (CMS) 17.6 mass%
[0259] Divinylbenzene (DVB: purity 57%, the remainder is ethylvinylbenzene) 8.2 mass%
[0260] Acrylonitrile (AN) 13.1 mass%
[0261] α-Methylstyrene (α-MeSt) 3.0 mass%
[0262] The following substances were mixed into 100 parts by mass of the monomer mixture:
[0263] Ethylene glycol diglycidyl ether 0.8 parts by mass
[0264] Acetyl tributyl citrate (ATBC) 17.4 parts by mass
[0265] Lauroyl peroxide (Peroyl L manufactured by NOF CORPORATION) 2.0 parts by mass
[0266] Further addition:
[0267] Vinyl chloride powder (ZEST P22 manufactured by SHINDAI-ICHI VINYL CORPORATION) 65.3 parts by mass
[0268] The mixture was then stirred for 2 hours to obtain a uniform polymerizable composition.
[0269] Next, the following high-density polyethylene monofilament woven fabric (PE33D 130 / 130) was prepared.
[0270] High-density polyethylene monofilament fabric (PE33D 130 / 130);
[0271] Mesh number: 130
[0272] Fiber diameter: 76μm (33 denier)
[0273] Thickness: 132μm
[0274] Opening rate: 37%
[0275] Bursting strength: 1.1MPa
[0276] The polymerizable composition obtained in the above manner was coated on the above-mentioned high-density polyethylene monofilament woven fabric (PE33D 130 / 130), and after covering both sides of the above-mentioned high-density polyethylene monofilament woven fabric with polyester film as a release agent, it was preheated at 45°C for 1 hour and then polymerized at 70°C for 3 hours.
[0277] The obtained film-like polymer was sulfonated with chlorosulfonic acid at 40° C. for 45 minutes to obtain a cation exchange membrane. The properties of the obtained cation exchange membrane are as follows.
[0278] Polyvinyl chloride content in cation exchange resin: 26.0%
[0279] Film thickness: 214μm
[0280] Ion exchange capacity: 2.0meq. / g-dry weight
[0281] Moisture content: 41%
[0282] Resistance: 2.3Ω·cm 2
[0283] Water seepage: 32ml / (m 2 hr)
[0284] Current efficiency: 78%
[0285] Bursting strength: 1.1MPa
[0286] As described above, each of the cation exchange membranes obtained in Examples 1 to 8 showed low resistance, and since the swelling of the ion exchange resin was suppressed, the amount of water permeation was small, and thus, excellent properties were exhibited.
[0287] <Comparative Example 1>
[0288] A cation exchange membrane was produced in the same manner as in Example 4, except that the amount of vinyl chloride powder (ZEST P22 manufactured by SHINDAI-ICHI VINYL CORPORATION) added to the monomer mixture was changed to 45.0 parts by mass.
[0289] The properties of the obtained cation exchange membrane are as follows.
[0290] Polyvinyl chloride content in cation exchange resin: 20.2%
[0291] Film thickness: 185μm
[0292] Ion exchange capacity: 2.4meq. / g-dry weight
[0293] Moisture content: 51%
[0294] Resistance: 1.5Ω·cm 2
[0295] Water seepage: 2102ml / (m 2 hr)
[0296] Current efficiency: 67%
[0297] Bursting strength: 0.8MPa
[0298] As described above, the cation exchange membrane obtained in Comparative Example 1 cannot sufficiently suppress swelling of the ion exchange resin because the polyvinyl chloride content in the cation exchange resin is too low. As a result, the amount of water permeation is larger than that of the membrane of Example 4.
[0299] <Comparative Example 2>
[0300] A cation exchange membrane was produced in the same manner as in Example 2 except that the amount of vinyl chloride powder (ZEST P22 manufactured by SHINDAI-ICHI VINYL CORPORATION) added to the monomer mixture was changed to 100.0 parts by mass.
[0301] The properties of the obtained cation exchange membrane are as follows.
[0302] Polyvinyl chloride content in cation exchange resin: 35.9%
[0303] Film thickness: 190μm
[0304] Ion exchange capacity: 2.0meq. / g-dry weight
[0305] Moisture content: 28%
[0306] Resistance: 3.6Ω·cm 2
[0307] Water seepage: 18ml / (m 2 hr)
[0308] Current efficiency: 87%
[0309] Bursting strength: 1.0MPa
[0310] As described above, the cation exchange membrane obtained in Comparative Example 2 has an excessively high polyvinyl chloride content in the cation exchange resin, and therefore is different from the membrane of Example 2 (resistance: 2.6 Ω·cm 2 ) compared to the original film, the resistance of the film increased significantly.
[0311] [Table 1]
[0312]
[0313] St:Styrene
[0314] DVB: divinylbenzene (purity 57%, the rest is ethylvinylbenzene)
[0315] AN: Acrylonitrile
[0316] CMS: p-Chloromethylstyrene
[0317] α-MeSt: α-methylstyrene
[0318] PVC1: Polyvinyl chloride powder (trade name: ZEST P22, average degree of polymerization 1050 / manufactured by SHINDAI-ICHI VINYL CORPORATION)
[0319] PVC2: Polyvinyl chloride powder (trade name: ZEST PQ135, average degree of polymerization 1350 / manufactured by SHINDAI-ICHIVINYL CORPORATION)
[0320] ATBC: Acetyl tributyl citrate
[0321] 40E: Ethylene glycol diglycidyl ether (trade name: Epolite 40E / made by Japan Kyoeisha Chemical Co., Ltd.)
[0322] PL: Lauroyl peroxide (trade name: Peroyl L / manufactured by NOF CORPORATION)
[0323] [Table 2]
[0324]
[0325] PE33d 120 / 120: High-density polyethylene monofilament fabric (thickness: 132μm, mesh number (vertical / horizontal): 120 / 120, fiber diameter: 76 / 76μm, opening rate: 41%, melting point: 130C)
[0326] PE33d 100 / 100: High-density polyethylene monofilament fabric (thickness: 132μm, mesh count (vertical / horizontal): 100 / 100, fiber diameter: 76 / 76μm, opening rate: 49%, melting point: 130℃)
[0327] PE33d 130 / 130: High-density polyethylene monofilament fabric (thickness: 132 μm, mesh size (vertical / horizontal): 130 / 130, fiber diameter: 76 / 76 μm, opening rate: 37%, melting point: 130°C)
[0328] (Other embodiments)
[0329] The above-mentioned embodiments are examples of the present invention, and the present invention is not limited to these examples, and known techniques, conventional techniques, and public techniques may be combined in these examples, or a part may be replaced. In addition, improved inventions that are easily conceivable by those skilled in the art are also included in the present invention.
Claims
1. A method for producing a cation exchange membrane used as a single membrane for electrodialysis, characterized in that: The method for producing the cation exchange membrane comprises an impregnation step and a copolymerization step. In the impregnation step, a polymerizable composition for forming a cation exchange resin is impregnated into the gaps of a substrate composed of a polyolefin woven fabric, wherein the polymerizable composition contains a monomer component, a polymerization initiator, and polyvinyl chloride, wherein the monomer component includes: a monomer having a functional group capable of introducing a sulfonic acid group or a sulfonic acid group; Crosslinking monomers, In the copolymerization step, after the impregnation step, the monomer components in the polymerizable composition for forming the cation exchange resin are copolymerized. The polymerizable composition for forming the cation exchange resin contains 55 parts by mass or more and 98 parts by mass of the polyvinyl chloride relative to 100 parts by mass of the monomer component, and the water permeation value of the cation exchange membrane measured using pressurized water at 0.1 MPa is 300 ml / (m 2 hr) or less, In the copolymerization step, the copolymerization is carried out at a temperature of 40° C. or higher and lower than 80° C. The substrate is made of polyethylene woven fabric. The monomer component also contains α-alkylstyrene, The amount of α-alkylstyrene is 1% by mass or more and 13% by mass or less based on the total amount of the monomer components.
2. The method for manufacturing a cation exchange membrane according to claim 1, characterized in that: The monomer having a functional group capable of introducing a sulfonic acid group or a sulfonic acid group is a styrene-based monomer having a functional group capable of introducing a sulfonic acid group or a sulfonic acid group.
Citation Information
Cited By
Ultrafiltration membrane device for waste alkali recovery
CN122479587A